The Effect of Track Distance and Emotional Intelligence on the Results Breaststroke Swimming - Wulandari, Oggi Susanti; Rahayu, Setya; Priyono, Bambang (Journal of Physical Education and Sports, 2021)
The reason for this study is that the length of the swimming training track at the Fish Aquatic Club and Mutiara Swimming Club is different. The purpose of this study was to ascertain the following: 1) to determine the effect of the swimming track's length of 25 and 35 meters on the results of breaststroke swimming. 2) examine the effect of high and low emotional intelligence on breaststroke swimming results. 3). investigated the effect of track length and emotional intelligence on breaststroke swimming performance. This research was using a two-by-two factorial design. The study population comprised twenty sons and twenty daughters from Mutiara swimming club and Fish Aquatic, with an average age of twelve years. The study was conducted between February 15 and 14, 2021. The Anova test revealed that the 35 meter track length (M = 29,72 second) had a significantly greater effect on swimming results than the 25 meter track length (M = 51,25 second), (F(1.36) = 260.178, p0.001, p2 = 0.878). There was a significant effect of high emotional intelligence (M = 35.19 second) swimming results (F (1, 36) = 63.030, p0.001, p2 = 0.636) compared to low emotional intelligence (M = 45,79 second). Track length and emotional intelligence have an effect on breaststroke swimming results (F(1.36) = 6.568, p0.015, p2 = 0.154). 15.4 percent of the variance in swimming exercise results. The findings of this study showed that there was a significant relationship between track length and emotional intelligence and breaststroke swimming performance.